Increase in number of healthy newborns breastfed within one hour of life after using quality improvement cycle at tertiary care centre in Goa - Naik, Viraj Ramesh; Cardoso, Pia Muriel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: It was evident from WHO Global Survey that, only 39.7% of newborns delivered via caesarean section were breastfed within 1 hour of life. By initiating breastfeeding within one hour of birth, over one million neonates can be saved each year globally. This study was conducted to analyse the retrospective secondary data to understand the reasons for delay in initiation of breastfeeding and to inculcate the methods used in quality improvement cycles for increasing the newborn babies breastfed within one hour of life. Methods: Our study was retrospective secondary data analysis. Data of 3 months was analysed and reasons of delayed breast feeding was analysed and how use of PDCA cycles to increase the breast feeding was analysed. Results: Our study showed that by using quality improvement tools, there was increase in the newborns breast fed within one hour of life from 73.75% to 94.95%. Conclusions: To improve the rates of breastfeeding within one hour of life, quality improvement cycles need to be constantly carried out and any hindrances should be tackled timely so as to ensure good neonatal outcomes.